Using systems thinking methodologies to address health care complexities and evidence implementation. Issue 1 (29th March 2022) - Khalil, Hanan; Lakhani, Ali
ABSTRACT: Background: Despite health care advances, artificial intelligence and government interventions aiming to improve the health and wellbeing of citizens, huge disparities and failures in care provision exist. This is demonstrated by the rising number of medical errors, increase in readmission rates and mortality rates, and the failure of many health systems to successfully cope with events, such as pandemics and natural disasters. This shortfall is in part because of the complexity of the health care system, the interconnectedness of various parts of service, funding models, the complexity of patients' conditions, patient and carer needs, and the clinical processes needed for patients via multiple providers. Objective: The objective of this paper is to describe the use of system thinking methodologies to address complex problems such as those in the public health and health services domains. Method: A description of the system thinking methodology and its associated methods including causal loop diagrams, social network analysis and soft system methodology are described with examples in the health care setting. Results: There are various models of knowledge translation that have been employed including the Joanna Briggs Institute model of implementation of evidence into practice, the triple C, and the Promoting Action on Research Implementation in Health Services. However, many of these models are neither scalable nor sustainable, and are most effective for localized projects implemented by trained clinicians and champions in relevant settings. System thinking is essentially a modelling process, which aims to create opportunities for change via an appreciation of perspective, and recognition that complex problems are a result of interconnected factors. The article argues that systems thinking applications need to move beyond that of addressing complex health issues pertaining to a population, and rather consider complex problems surrounding the delivery of high-quality health care. Conclusion: It is important that methods to implement systems thinking methodologies in health care settings are developed and tested.